Spectrum of Salivary Gland Disorders at a Tertiary Care Hospital in Central Lahore (Journal of Fatima Jinnah Medical University, 2018)
Background: Salivary glands disorders remain a frequent presentation in general surgery outpatient departments. The disease spectrum varies from inflammatory pathology, ductal obstruction to benign and malignant neoplasms. Pleomorphic adenoma still remains on the top with its attendant risk of damage to facial nerve as the most feared complication. Selection of appropriate preoperative diagnostic investigation and suitable surgical procedure are the mainstay to achieve acceptable outcome. The aims of this study was to determine demographic details, clinical and histopathological features of salivary gland disorders and outcome of surgery at a tertiary care hospital in Central Lahore.Patients and Methods: This prospective observational study was carried out in the Department of Surgery, Fatima Jinnah Medical University, Sir Ganga Ram Hospital Lahore over 4 years period. Sixty-one consecutive patients were admitted with various salivary gland disorders from January 2013 till December 2017. All patients were assessed by thorough history, physical examination and relevant investigations. Fine needle aspiration cytology was performed in all cases. All patients underwent surgery. Postoperative morbidity and mortality were recorded. Histopathology report was compared with preoperative diagnostic investigations to assess the investigation of choice. Follow up on all patients is available for variable period of time.Results: Age of the patients ranged from 15 to 79 years (mean 34±1.4 years). There were 24 males and 37 females, male to female ratio of 1:1.65. Most of the patients (60.3%) presented in 2nd and 3rd decades. Swelling was the commonest clinical presentation and mean duration was 2±2.2 years. Pleomorphic adenoma was the most common benign tumor (86.2%), affecting parotid gland in 95.55% of cases. Mucoepidermoid carcinoma was the most frequent salivary gland malignant tumor (7%), predominantly affecting submandibular glands.Conclusion: Salivary gland disorders are more frequent in middle age female population. Benign tumors remain the most common salivary gland pathology. Pleomorphic adenoma is the most common benign salivary gland tumor affecting predominantly parotid gland. Mucoepidermoid carcinoma is the commonest malignant salivary neoplasm and affects predominantly submandibular glands.
Keywords: salivary glands, presentation, tumors, histopathology, surgery, outcome, complications.